Desarrollo de la educación superior en el Ecuador en los años 2000 - Cecilia , Marcillo (2021)
The progress of a country will always depend on the education of its citizens, for this reason, talking about education in general and higher education in particular is relevant because of the inﬂ uence it has on the performance of each of the academy’s professionals. is article presents the development of higher education in the 2000s starting from a religious, cultural and above all political review